Genome editing in the edible fungus Poria cocos using CRISPR-Cas9 system integrating genome-wide off-target prediction and detection - Xie, Zhenni; Zhong, Can; Liu, Xiaoliu; Wang, Ziling; Zhou, Rongrong; Xie, Jing; Zhang, Shuihan; Jin, Jian (Frontiers in Microbiology, 2022)
Poria cocos is an important edible and medicinal fungus for a long history. However, the lack of adequate genetic tools has hindered molecular genetic research in and the genetic modification of this species. In this study, the endogenous U6 promoters were identified by mining data from the P.cocos genome and the promoter sequence was used to construct a sgRNA expression vector pFC332-PcU6. Then, the protoplast isolation protocol was developed and the sgRNA-Cas9 vector was successfully transformed into the cells of P. cocos via PEG/CaCl₂-mediated transformation approach. Off-target sites were genome-widely predicted and detected. As a result, the target marker gene ura3 was successfully disrupted by the CRISPR-Cas9 system. This is the first report of genome editing in P. cocos using CRISPR-Cas9 system integrating genome-wide off-target prediction and detection. These data will open up new avenues for the investigation of genetic breeding and commercial production of the edible and medicinal fungus.